Evaluation of 'see-see and treat' strategy and role of HIV on cervical cancer prevention in Uganda - Sandin Sven; Mirembe Florence; Mutyaba Twaha; Weiderpass Elisabete (BMC, 2010)
Abstract Background There is scant information on whether Human Immunodeficiency Virus (HIV) seropositivity has an influence on the outcome of treatment of precancerous cervical lesions using cryotherapy. We studied the prevalence of cervical abnormalities detectable by visual inspection and cervical lesions diagnosed by colposcopy according to HIV serostatus and described the outcomes of cryotherapy treatment. Methods Trained nurses examined women not previously screened for cervical cancer using visual inspection with acetic acid (VIA) and Lugol's iodine (VILI) in two family planning/post natal clinics in Kampala, Uganda, from February 2007 to August 2008. Women with abnormal visual inspection findings were referred for colposcopic evaluation and HIV testing. Women with precancerous cervical lesions detected at colposcopy were treated mainly by cryotherapy, and were evaluated for treatment outcome after 3 months by a second colposcopy. Results Of the 5 105 women screened, 834 presented a positive screening test and were referred for colposcopy. Of these 625 (75%) returned for the colposcopic evaluation and were tested for HIV. For the 608 (97.5%) women in the age range 20-60 years, colposcopy revealed 169 women with cervical lesions: 128 had inflammation, 19 had low grade squamous intraepithelial lesion (LGSIL), 13 had high grade squamous intraepithelial lesion (HGSIL), 9 had invasive cervical cancer and 2 had inconclusive findings. Detection rates per 1 000 women screened were higher among the older women (41-60 years) compared to women aged 20-40 years. They were accordingly 55% and 20% for inflammation, 10% and 2% for LGSIL, 5% and 2% for HGSIL, 6% and 1% for invasive cervical cancer. Of the 608 women, 103 (16%) were HIV positive. HIV positivity was associated with higher likelihood of inflammation (RR = 1.7; 95% CI: 1.2-2.4). Conclusions Detection rates were higher among older women 41-60 years. Visual inspection of the cervix uteri with acetic acid (VIA) and Lugol's iodine (VILI) used as a sole method for cervical cancer screening would entail significant false positive results. HIV seropositivity was associated with a higher prevalence of inflammatory cervical lesions. In view of the small numbers and the relatively short follow up time of 3 months, we could not make an emphatic conclusion about the effect of HIV serostatus on cryotherapy treatment outcome.